2019
DOI: 10.1101/655852
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

How a mouse licks a spout: Cortex-dependent corrections as the tongue reaches for, and misses, targets

Abstract: Precise control of the tongue is necessary for drinking, eating, and vocalizing. Yet because tongue movements are fast and difficult to resolve, neural control of lingual kinematics remains poorly understood. We combine kilohertz frame-rate imaging and a deep-learning based artificial neural network to resolve 3D tongue kinematics in mice performing a cued lick task. Cue-evoked licks exhibit previously unobserved fine-scale movements which, like a hand searching for an unseen object, were produced after misses… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 34 publications
1
7
0
Order By: Relevance
“…Optogenetic inhibition of ALM impaired both the length of each lick and the ability to direct licks away from the midline. These results partly support recent work showing that inhibition of ALM impairs aspects of tongue kinematics in a cued-licking task 34 . Electrophysiological recordings in ALM revealed strong encoding of θ but surprisingly not L or L' (which can indirectly produce L ).…”
Section: Discussionsupporting
confidence: 90%
“…Optogenetic inhibition of ALM impaired both the length of each lick and the ability to direct licks away from the midline. These results partly support recent work showing that inhibition of ALM impairs aspects of tongue kinematics in a cued-licking task 34 . Electrophysiological recordings in ALM revealed strong encoding of θ but surprisingly not L or L' (which can indirectly produce L ).…”
Section: Discussionsupporting
confidence: 90%
“…Manual dexterity of mice during food-handling interaction between the hands and orofacial apparatus. A future challenge is to understand how rapid, fine-scale movements of the tongue [31], teeth/jaws, lips, and other buccal musculature are orchestrated with those of the hands, and particularly the thumbs.…”
Section: Discussionmentioning
confidence: 99%
“…We demonstrated that CS and ALM had greater increases in calcium activity associated with body grooming than with face grooming (Fig.1, Fig.3), and our optogenetic stimulation paradigms often produced behaviors that resembled body grooming (turning inward towards the body and performing tongue movements), as opposed to face grooming (raising paws to face). This selectivity of CS for body grooming may reflect the known role of ALM in anticipatory and ingestive licking behavior in trained tasks that require consumption of liquid (Bollu et al, 2019;Li et al, 2015). Here, in an untrained context, we observed grooming and grooming-like behaviors that also involved licking.…”
Section: Specialization Of Alm-cs Circuit For Grooming May Partially mentioning
confidence: 53%
“…Prior work has demonstrated that anterior M2/anterior lateral motor area (ALM), one of the major cortical inputs to CS (Corbit et al, 2019), is associated both with appropriate sequencing of movements during trained tasks and with generating licking movements (Bollu et al, 2019;Li et al, 2015;Rothwell et al, 2015). ALM may therefore be uniquely suited for guiding selection of spontaneously generated behaviors such as body grooming.…”
Section: Alm Shows Increased Activity Specifically At Grooming Onsetmentioning
confidence: 99%